Ambrosio Oropeza: El ideario constitucional de un civil (Mayéutica Revista Científica de Humanidades y Artes, 2021)
Like all births of the gestated in Venezuela, we receive with rejoicing this work by the authorship of our historian Reinaldo Rojas: the book AmbrosioOropeza, The construction of Venezuelan Constitutional Law, A biography intellectual, which was born in work meetings of Project Roscio; he was inour hearts and ideas and at Universitas Fundación he found his first steps with one of the jobs that would be taken as a flag.